Exploring factors influencing nurses’ attitudes towards their role in dental care - Gaffar B; Bakhurji E; AlKhateeb R; AlHashim H; AlGaoud H; AlDaamah Z; AlSaleh J; Aldamanhori R; AlHamid S; AlBarrak A; Siddiqui IA; Virtanen JI. (United States, 2025)
Background: The burden of oral disease requires collaboration between health care professionals. Nurses are frequently exposed to patients and can play a vital role in prevention of oral diseases. This study aimed to investigate nurses' attitudes towards their role in dental care and its associated factors.
Methods: This cross-sectional, survey-based study recruited a total of 525 nurses in Eastern Saudi Arabia, using a snow-ball sampling technique. Data was collected using an online, pre-validated 40-item questionnaire with four domains (attitudes, knowledge, practices, and demographic data).
Results: Nurses showed satisfactory attitudes (52.8 ± 8.2) and average knowledge (13.4 ±3.9). More than two thirds (70.3%) reported responding to patients' questions about oral health conditions, 47.1% and 19.7% conducted oral health screening and education respectively. Referral practices were reported by 266 (50.7%) of the participants with pain being the main reason for referrals. Attending lectures/ trainings on oral health and having a formal education about oral health were significantly associated with nurses' positive attitudes towards their role in dental care (P<0.001). Conducting oral health screening or education were also significantly associated with positive attitudes (P = 0.001).
Conclusion: Positive attitudes were observed among those with undergraduate oral health backgrounds, in continuous education, and those who were involved in oral health screenings. There is a need for under and postgraduate inclusion of oral health training in nurses' education.